2022
DOI: 10.1007/s11682-022-00651-8
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics of Resting-state Functional Networks and Cognitive Functioning following Systemic Treatment for Breast Cancer

Abstract: Many women with breast cancer suffer from a decline in memory and executive function, particularly after treatment with chemotherapy. Recent neuroimaging studies suggest that changes in network dynamics are fundamental in decline in these cognitive functions. This has, however, not yet been investigated in breast cancer patients. Using resting state functional magnetic resonance imaging, we prospectively investigated whether changes in dynamic functional connectivity were associated with changes in memory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…It was suggested that not only chemotherapy, but also cancer itself could disrupt the functional connectivity measured with resting- or task-state functional magnetic resonance imaging (fMRI) [ 11 , 32 , 33 ]. For the patients with breast cancer before receiving any treatment, the lower whole-brain functional connectivity, the greater decline in cognitive function [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that not only chemotherapy, but also cancer itself could disrupt the functional connectivity measured with resting- or task-state functional magnetic resonance imaging (fMRI) [ 11 , 32 , 33 ]. For the patients with breast cancer before receiving any treatment, the lower whole-brain functional connectivity, the greater decline in cognitive function [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the patients with breast cancer before receiving any treatment, the lower whole-brain functional connectivity, the greater decline in cognitive function [ 33 ]. These aberrant functional connectivities were also considered to be relevant to the memory impairment and fatigue [ 11 , 32 ]. The presence of neuropsychiatric symptoms among patients with hematological cancer was supposed to be more likely than those with solid tumor [ 6 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cognitive deficits have been observed in neuropsychological studies even years after the cessation of chemotherapy. Women complain of concentration problems, difficulties with finding words, and trouble remembering new information [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%